PERAN KEPUASAN KOMUNIKASI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI - , SELLVY ANNEKINDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Employeesâ organizational commitment is the main aspect to sustain organizationâs productivity and to reach organizationâs goal. Employees with low organizational commitment will impact in low productivity, therefore, leaders must be able to overcome the issue. Communication satisfaction and transformational leadership are factors that may predict employeesâ organizational commitment. The aim of this study is to predict the effect of communication satisfaction and transformational leadership towards organizational commitment. Research design used in this research is survey study of 203 questionnaires are given to Rumah Sakit Happy Landâs employees. Data analysis used to test the hypotheses is multiple linear regression, which results in the value of coefficient determination (RÂ²) = 0.271, which means communication satisfaction and transformational leadership have 27.1% impact towards organizational commitment. As for each variable, communication satisfaction give 19.8% impact and transformational leadership give 7.3% impact towards organizational commitment. Keywords: organizational commitment, communication satisfaction, transformational leadership